Integrating Mern Technology In E-Learning: Opportunities And Challenges For SMEs - Satriyo, Bayu Dwi; Fitriyadi, Farid; Retnoningsih, Dwi (International Journal of Computer and Information System (IJCIS), 2024)
Abstract    This article develops an E-Learning application called BrandBiz using MERN technology (MongoDB, Express, React, and Node.js) to help MSMEs understand product branding. This application also uses Progressive Web App (PWA) technology for flexibility of use on various devices. The research methodology involves literature studies and user testimonials to collect data and measure the effectiveness of the application. As a result, BrandBiz provides login, registration, selection and learning of educational paths, quizzes, and feedback features, which are accessed via https://www.brandbiz.site/. BrandBiz helps MSMEs improve their product branding and marketing knowledge, potentially increasing their income. This application offers innovative and easily accessible educational solutions, supporting local economic growth in Indonesia.